The Future of Human Resources and Digital Trend Phenomenon in Indonesian Business Practices: Review Literature - SOSROWIDIGDO, SURYANTO; ARIFIN, ANTONI LUDFI; PRANOGYO, ANTAIWAN BOWO; RAMADITYA, MUHAMMAD; SATRIADI (The journal of contemporary issues in business and government, 2021)
Efforts to understand the increasing business progress by increasing human resources with digital technology through a systematic review were made. We have carried out with the results, among others, that we have systematically reviewed publications confirming that efforts to increase the capacity of human business resources and public service organizations through optimization of digitalization are the right steps and very reasonable. This is because the effectiveness and superiority of technology to this day are unmatched. We seek to find this understanding with a descriptive qualitative approach review design. We searched secondary sources of data through the Google search engine for two data sources; Google Scholar and ERIC publications. For our data to be updated, we choose between the 2010 to 2020 issues except fundamental theory data. Thus these findings become input for business people, academics, and policymaking.